Stakeholder perception of reverse logistics practices on supply chain performance. (7th August 2020) - Pushpamali, NNC; Agdas, Duzgun; Rose, Timothy M.; Yigitcanlar, Tan
Abstract: Managing supply chain performance is essential for value generation to stakeholders. Nonetheless, this process has become overly complicated due to environmental concerns that lead to policy changes, customer preferences, and business activities. Reverse logistics is an environmentally friendly practice that can be critical in improving the environmental performance of construction operations. This paper examines the perceived role of reverse logistics practices on supply chain performance criteria—for example, cost, quality, time, flexibility, and environment. Semistructured in‐depth interviews were conducted with 15 senior industry experts from South East Queensland, Australia. Interview transcripts were analyzed by coding, categorizing, and identifying the interconnected relationships among concepts. In general, the experts perceive that reverse logistics practices significantly reduce the sourcing cost of materials compared with new materials. When used materials meet industry specifications, they are expected to have a similar performance without affecting the construction time or the overall quality of the project while protecting the environment. Nevertheless, the flexibility is found to be somewhat difficult. It is likely that reverse logistics can be instrumental in construction should the industry uptake be substantial with an emphasis on used material quality and acceptance criteria. Hence, a quantitative analysis is encouraged for future research.